SIKAP PEMIRSA TERHADAP MOTTO LIPUTAN 6 PETANG SCTV:AKTUAL, TAJAM, TERPERCAYA - alkatiri, alkatiri (Jurnal Sosial Humaniora, 2011)
The present research is aimed to: 1. identify individual perception or attitudes towards Ã¢â¬â¢Liputan 6 Petang SCTVÃ¢â¬â¢, a news program with its motto: actual, critical and trustworthy. (2) identify the interrelation between individual characteristic with audiencesÃ¢â¬â¢ opinions towards the motto of actual, critical and trustworthy (3) identify relationship between communication attitudes and broadcasting design towards audiencesÃ¢â¬â¢ opinion on the Liputan 6 PetangÃ¢â¬â¢s motto of actual, critical and trustworthy (4) identify attitudes and reactions with audiencesÃ¢â¬â¢ opinion towards the Liputan 6 PetangÃ¢â¬â¢s motto of actual, critical and trustworthy. This research utilizes correlation description research method and 150 samples. A number of variables that measured including respondentsÃ¢â¬â¢ characteristics, communications attitudes, broadcasting design, audiencesÃ¢â¬â¢ opinions towards Liputan 6 PetangÃ¢â¬â¢s motto, as well as audiencesÃ¢â¬â¢ reaction after viewing Liputan 6 Petang. Data were analysed based on Spearman correlation coefficient. Research findings show that: 1. there is a correlation between audiencesÃ¢â¬â¢ characteristics in Jabotabek region with some parts of opinions of Liputan 6 PetangÃ¢â¬â¢s motto. 2. There is a significant correlation between audiencesÃ¢â¬â¢ communication attitudes towards Liputan 6 PetangÃ¢â¬â¢s motto 3. In general there is a correlation between program design with Jabotabek audiencesÃ¢â¬â¢ opinion towards Liputan 6 PetangÃ¢â¬â¢s motto. 4. There is a significant correlation a part of audiencesÃ¢â¬â¢ opinions towards Liputan 6 Petang SCTV with audiencesÃ¢â¬â¢ attitudes and reactions.